CIVIL SOCIETY AND POLITICAL TRANSITIONAL: A SYSTEMATIC LITERATURE REVIEW (SLR) - Imelda Dhea Margareta; Salahudin; Daus (Governance, 2024)
The current political transitional makes people dependent on the government, because of this people want change to occur in their country. By choosing a good leader, a country can improve. But there are still many cases of very rampant money politics, which are less efficient to carry out. This research aims to make civil society aware to avoid transitional politics because this dangerous behavior is less ethical in choosing leaders who actually only want power but do not understand the situation of their people. The research method applied in this research is a systematic literature review using several scientific articles sourced from the Scopus database. Review articles using the Vosviewer application. The results of the research reveal that there are still many perpetrators who still carry out money politics with the public, and the perpetrators of bribery are not only legislative institutions but also executive institutions which also play a role in this problem. The results of this research contribute to the development of a research roadmap on civil society and transitional politics. People should not accept bribery because it is bad behavior and it is written in the law regarding bribery and it is very detrimental to themselves and also detrimental to the state. The limitation of this research is that the articles used only come from the Scopus database so that the research findings cannot comprehensively describe civil society and political transitions throughout the world. Future research needs to use scientific articles sourced from other reputable international databases, such as Web of Science and Dimensionds Scholars. So there are still many transitional political actors, usually this behavior is supported by their political parties, and people are also easily tempted by invitations in exchange for gifts, usually in the form of basic necessities or money.